Physical properties of undisturbed tropical peat soil at Pekan District, Pahang, West Malaysia - Abdul, Wahab; Muzamir, Hasan; Faradiella, Mohd Kusin; Zaidi, Embong; Uz Zaman, Qamar; Zaheer Uddin, Babar; Muhammad Syamsul Imran, Zaini (Penerbit UTHM, 2022)
Peat soil are considered soft soil with having weak characteristics such as low shear strength, high moisture content, and compressibility. Construction perspective, peat soil is considered as unstable soil due to its poor engineering properties. It may cause an extensive loss in road or building construction projects. The key objectives of the current study are to examine the physical properties of peat soil including shear strength, liquid limit, moisture content, organic content, pH, and dry density of peat soil in Pekan district. The peat samples were collected from Kampung Bahru (KB), Kampung Lancing I (KLI), and Kampung Lancing II (KL II), Pekan District, Pahang, Malaysia. The finding indicates that the shear strength (kPa) for was measured in between 7.2 to 8.2 kPa. The water content was recorded 537.10 % to 635.28 %. The liquid limit was examined 137.638% to 152.540 %, the maximum dry density was examined 6.68 x 10-7 kg/cm3 to 7.99 x 10-7 kg/cm3. The average organic content was calculated as approximately 95.88 % to 98.48 %. In comparison with previous study, its indicated that the investigated peat soil in Pekan area is mainly content with lower shear strength, high water content, liquid limit, and low density, resulting in low strengthening properties. Based on the examined physical properties, its specified that peat did not have adequate stability as a road or building foundation. Strengthen of peat are highly recommended for any types of construction on peatland in Pekan district, Pahang, Malaysia.